Histone Deacetylase Inhibitors: Advancing Therapeutic Strategies in Hematological and Solid Malignancies - Ellis, Leigh (MDPI, 2010)
Advancement in the understanding of cancer development in recent years has identified epigenetic abnormalities as a common factor in both tumorigenesis and refractory disease. One such event is the dysregulation of histone deacetylases (HDACs) in both hematological and solid tumors, and has consequently resulted in the development of HDAC inhibitors (HDACI) to overcome this. HDACI exhibit pleiotropic biological effects including inhibition of angiogenesis and the induction of autophagy and apoptosis. Although HDACI exhibit modest results as single agents in preclinical and clinical data, they often fall short, and therefore HDACI are most promising in combinational strategies with either standard treatments or with other experimental chemotherapies and targeted therapies. This review will discuss the induction of autophagy and apoptosis and the inhibition of angiogenesis by HDACI, and also pre-clinical and clinical combination strategies using these agents.